Pengaruh Promosi Digital, Word of Mouth, dan Product Quality Terhadap Kepuasan Konsumen Produk Daily Care - Sonia Maylany Fatul Islamia; Mataji Mataji (Yayasan Cendekia Gagayunan Indonesia, 2026)
The purpose of this research is to examine how PT Tempo Scan Group's daily care product marketing in North Surabaya is influenced by digital promotion, word of mouth, and product quality in relation to customer satisfaction. The researchers in this study used a quantitative technique based on survey data. Questionnaires were sent out to customers who had utilised PT Tempo Scan Group's daily care items in order to gather data. One hundred participants were selected using a purposive sampling method. Multiple linear regression with conventional assumption tests (e.g., normalcy, multicollinearity, and heteroscedasticity) and hypothesis testing (e.g., t-test and F-test) were used to analyse the data. There is a favourable and statistically significant relationship between customer happiness and digital marketing, word of mouth, and product quality. Among these factors, product quality was determined to have the greatest impact on customer satisfaction. These results point to the importance of positive consumer communication, consistent product quality, and successful digital promotional techniques in increasing consumer satisfaction in the daily care product business.